HISTORICAL ANALYSIS OF THE POLICY OF INTERETHNIC TOLERANCE AND SOCIAL EQUALITY IN UZBEKISTAN IN THE XX-XXI CENTURIES (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The late 20th - early 21st centuries were a period of profound social, political, and economic transformations for the Central Asian region, in particular, for Uzbekistan. The collapse of the Soviet Union led to the formation of migration flows in this region and the construction of interethnic relations on a new basis. The purpose of this scientific research is to analyze the formation, content, and main trends of the policy of interethnic tolerance and social equality in Uzbekistan during this historical period. In the study of this issue, special attention is paid to the evolution of the concept of tolerance in the post-Soviet space, the specifics of national policy in the Soviet period, and the processes of ethnic identity (ethnic identification) in the context of modern globalization.